A dual-biomimetic knitted fabric with a manipulable structure and wettability for highly efficient fog harvesting. Issue 1 (13th December 2021) - Yu, Zhihua; Li, Shuhui; Liu, Mingming; Zhu, Ruofei; Yu, Mengnan; Dong, Xiuli; Sun, Yaxin; Fu, Shaohai
Abstract : A bio-inspired fabric with wedge-shaped tracks and patterned wettability was fabricated using knitting technology. The dual-biomimetic knitted fabric exhibited excellent fog harvesting performance. Abstract : The shortage of freshwater severely constrains economic development and social security worldwide. Bio-inspired functional fog-harvesting devices (FHDs) have been broadly exploited to tackle this global challenge. Despite the great advances achieved in FHDs, efficient and large-scale water harvesting is still hindered by some inherent limitations: (1) a rational structure should be designed to maximize the function of the separated hydrophilic and hydrophobic regions, (2) simple, low-cost and mature manufacturing technology can better realize the large-scale production of FHDs. Here, inspired by the unique wettability of Namib desert beetles and the wedge-shaped structure of leaf veins, we prepared a dual-biomimetic tuck fabric with a manipulable structure and wettability using knitting technology, which greatly enhanced the fog capture velocity and directional water transportation. The influences of different structures and wettability on fog capture and droplet transportation efficiency have been systematically investigated. Moreover, massive theoretical models were proposed to reveal the fog harvesting mechanism. The optimized FHD exhibited rapid and highly efficient fog harvesting capacity (5424 mg h −1 cm −2 ). In addition, the prepared FHD showed excellent mechanical strength and durability, enabling low-cost and large-scale production. Thus, this work reinforces the understanding of the fundamental research and significantly promotes the practical applications of functional fog-harvesting devices.